2018
DOI: 10.1097/acm.0000000000002387
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a National Competency-Based Medical Education Initiative in Family Medicine

Abstract: Triple C has been successfully implemented across Canada but in differing ways and with different impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…Family medicine was one of the earliest adopters of CBME framework in Canada and the United States with its programs being implemented into residency training on a nationwide scale. 12,16,22,25,26 The challenge is that the studies that have focused on examining competency-based assessment tools (eg, identifying challenges, providing criteria, basic principles, and guidance for good assessment), 4,6,11,[27][28][29][30] have not paid sufficient attention to the overall implementation of assessment practices, particularly in family medicine. In other words, there are no studies that have thematically and systematically synthesized the current family medicine literature pertaining to the overall CBME assessment implementation and identified gaps in existing knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Family medicine was one of the earliest adopters of CBME framework in Canada and the United States with its programs being implemented into residency training on a nationwide scale. 12,16,22,25,26 The challenge is that the studies that have focused on examining competency-based assessment tools (eg, identifying challenges, providing criteria, basic principles, and guidance for good assessment), 4,6,11,[27][28][29][30] have not paid sufficient attention to the overall implementation of assessment practices, particularly in family medicine. In other words, there are no studies that have thematically and systematically synthesized the current family medicine literature pertaining to the overall CBME assessment implementation and identified gaps in existing knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Authors in other contexts have also reported that educational innovations have resulted in an underappreciated increased administrative requirement necessitating additional time and effort from educational leaders. 14,15 We think this increased education-based administration, with its adverse impact on educational supervisors, deserves greater recognition in the design and implementation of future educational innovations in the workplace. Within our participants' context, we think ANZCA ought to advocate for increased time and administrative support for Supervisors of Training while seeking to simplify the administrative requirements where possible.…”
Section: Discussionmentioning
confidence: 99%
“…This led to some inconsistencies across programs. 13 As our experience with CBME deepens, we observe that competence, while necessary, may be insufficient on its own to ensure preparedness and uptake of comprehensive practice. What else is required?…”
Section: Lessons Learned?mentioning
confidence: 96%
“…This cultivated a sense of ownership, professional identity, purpose, and enthusiasm within the family medicine teaching community and spawned a generation of educational leaders. 13 Despite these important accomplishments, CBME does not appear to have moved the needle on our social accountability goals. Rural, indigenous, and inner-city populations are still underserved, with a maldistribution of family physicians and the scopes of practice and practice intentions of our graduates continuing to narrow.…”
Section: What Is Our Story?mentioning
confidence: 99%